"If Rainbows Were Everywhere": Nonmetropolitan SGM Youth Identify Factors That Make Communities Supportive. Issue 4 (2nd October 2018) - Paceley, Megan S.; Thomas, Margaret M. C.; Toole, Jackie; Pavicic, Elise
ABSTRACT: Sexual and gender minority (SGM) youth in nonmetropolitan communities face marginalization due to their SGM identities. Community support may mitigate the negative outcomes associated with marginalization. Using the strengths perspective, this study investigated the factors SGM youth identify as making their communities supportive. Interviews were conducted with SGM youth to explore their perceptions of their community, community climate, and the factors that contribute to making communities supportive to SGM youth. Findings revealed four supportive community factors: supportive people, SGM visibility, SGM resources and education, and SGM-inclusive policies. Implications include creating SGM resources and providing professional training on SGM issues.